The Authority of the Honorary Regional Notary Assembly in Relating to Inspection of Notary of Move of Position Area by Law Enforcement Officer - Ahmad Laduni Arif Rahman; Rusdianto Sesung (Unram Law Review, 2017)
Implementation authority of the Honorary Regional Notary Assembly in giving approval and/or rejection of a request for approval from law enforcement (Investigator, Public Prosecutor, or Judge) to a Notary who has moved the office area in relation to the deed he / she has made with the criminal case. Cause 2 (two) fundamental questions relating to the authority of the Honorary Regional Notary Assembly authorized to grant approval and / or rejection of the application for approval and the determination of the time limit of no later than 30 (thirty) working days for the Honorary Regional Notary Assembly shall provide the answers. From the results of the research note that based on legislation, authority to grant approval to a Notary who moves to office of the apparatus of law enforcement officers is the jurisdiction of the Honorary Regional Notary Assembly in which the Notary's position is concerned. This means that such provisions shall apply directly to the determination of a maximum 30 (thirty) working day time limit for the Honorary Regional Notary Assembly giving the answer counted at the receipt of the summoning letter by the law enforcement apparatus.